PELATIHAN PERANGKAT LUNAK SIMULASI SCILAB BAGI SISWA/SISWI SMK PENERBANGAN AAG YOGYAKARTA - Astuti, Yenni; Cahya Risti Putri, Amanda; Baskoro, Zaana (Fakultas Teknologi Informasi dan Industri Unisbank, 2024)
In this era of information technology, there is a lot of simulation software that can be used to make it easier for users to understand and find solutions to various problems. One of these simulation software is a software that is open source or open for anyone to use and develop. for example Scilab. SMK Penerbangan AAG is a vocational high school that focuses on aviation area. One of its missions is to implement the international standard education. To realizing, it requires support from many parties. International standard education will be very good if it is accompanied by the use of Information Technology and Computers in solving engineering problems. For this reason, this Community Service takes the theme of simulation software training. In this case, Scilab software was chosen to support the use of information technology for engineering problems.